Counseling Teacher Social Support Influence Career Optimism Differently Based on Gender in Vocational High School - Nugroho, Alnico Imam; Samudera, Arung; Herwin, Herwin (Bulletin of Counseling and Psychotherapy, 2024)
Vocational high school graduates are prepared to go straight into the workforce but there is a problem with high unemployment. The purpose of this study was to examine the effect of counseling teacher social support and gender on career optimism of vocational high school students. This study was conducted in March 2024, involved 348 students of Vocational High School. Using multiple regression analysis with the results showed that counseling teacher social support and gender had a significant effect on career optimism with a sig of 0.000 (sig<0.05). The social support of counseling teachers was also tested for each aspect, only instrumental support had an effect on students' career optimism and men have higher career optimism. The findings reveal that there is a need for social support from counseling teachers in order to influence students' career optimism to face the world of work after graduating from school.